Arabidopsis transcriptional response to extracellular Ca2+ depletion involves a transient rise in cytosolic Ca2+. Issue 2 (8th July 2014) - Wang, Jing; Tergel, Tergel; Chen, Jianhua; Yang, Ju; Kang, Yan; Qi, Zhi
Abstract Ecological evidence indicates a worldwide trend of dramatically decreased soil Ca2+ levels caused by increased acid deposition and massive timber harvesting. Little is known about the genetic and cellular mechanism of plants' responses to Ca2+ depletion. In this study, transcriptional profiling analysis helped identify multiple extracellular Ca2+ ([Ca2+]ext) depletion‐responsive genes in Arabidopsis thaliana L., many of which are involved in response to other environmental stresses. Interestingly, a group of genes encoding putative cytosolic Ca2+ ([Ca2+]cyt) sensors were significantly upregulated, implying that [Ca2+]cyt has a role in sensing [Ca2+]ext depletion. Consistent with this observation, [Ca2+]ext depletion stimulated a transient rise in [Ca2+]cyt that was negatively influenced by [K+]ext, suggesting the involvement of a membrane potential‐sensitive component. The [Ca2+]cyt response to [Ca2+]ext depletion was significantly desensitized after the initial treatment, which is typical of a receptor‐mediated signaling event. The response was insensitive to an animal Ca2+ sensor antagonist, but was suppressed by neomycin, an inhibitor of phospholipase C. Gd3+, an inhibitor of Ca2+ channels, suppressed the [Ca2+]ext‐triggered rise in [Ca2+]cyt and downstream changes in gene expression. Taken together, this study demonstrates that [Ca2+]cyt plays an important role in the putative receptor‐mediated cellular and transcriptional response to [Ca2+]ext depletion of plant cells.